A clinical study of mode of delivery and perinatal outcome in iligohydramnios - Hangarga, U. S.; Kulkarni, V. G.; Nikitha, . (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To evaluate intrapartum sequale of sonographically diagnosed Oligohydrominos such as rate of caesarean section, fetal distress and condition of the new born. Methods: This Prospective observational study was conducted in the department of obstetrics and Gynecology, Navodaya Medical College Hospital and Research Centre between June 2015 to December 2016. The antenatal women with gestational age more than 34 weeks and above, attending our OPD or labor room were included in this study. Results: A total of 140 cases of Oligohydromnias were selected for present study and outcome were assessed. The mean maternal age is 24.42 years. 32.14% cases have delivered vaginally, 67.82% patients went for caesarean sections, 10.7% of babies needed NICU care and 1 was still birth. No adverse maternal complications were observed during the study. Conclusions: Oligohydromnia is one of the frequent complications during labor. The risk of muconium staining of liquor, intrapartum fetal distress, operative delivery and NICU admissions are more in Oligohydromnia cases.